Anharmonic vibrational spectra from double incremental potential energy and dipole surfaces. Issue 5 (15th January 2018) - Madsen, Diana; Christiansen, Ove; König, Carolin
Abstract : Using incremental approaches, size limitations for property surface generations are pushed significantly, enabling accurate large molecule anharmonic vibrational spectra calculations. Abstract : We extend the fragmentation-based double incremental expansion in FALCON coordinates (DIF) and its linear-scaling analogue [C. König and O. Christiansen, J. Chem. Phys., 2016, 145, 064105] to dipole surfaces. Thereby, we enable the calculation of intensities in vibrational absorption spectra from these cost-efficient property surfaces. We validate the obtained potential energy and dipole surfaces by vibrational spectra calculations employing damped response theory for correlated vibrational coupled cluster wave functions. Our largest calculation on a hexa-phenyl includes all 180 vibrational degrees of freedom of the system, which illustrates the potential of both the DIF schemes for property surface generation and the use of damped response theory from high-dimensional correlated vibrational wave functions. Generally, we obtain good agreement between the spectra calculated from the DIF property surfaces and the non-fragmented analogues. Moreover, when adopting suitable electronic structure methods, good agreement with respect to the experiment can be obtained, as shown for the example of 5-methylfurfural and RI-MP2. In conclusion, our results illustrate that the presented scheme with linearly scaling surfaces enables high quality spectra, as long as reasonably sized fragments can be defined. With this work, we push the realistic limits of vibrational spectra calculations from vibrational wave function methods and accurate electronic structure calculations to significantly larger systems than currently accessible.